Government Strategy in Establishing Gambang Semarang as the Artistic Identity of Semarang City - Pamarti Ningrum, Indrianna Dyah; Slamet Haryono; Syahrul Syah Sinaga (Catharsis, 2024)
Law Number 5 of 2017 concerning Cultural Advancement is a reference for the Department of Culture and Tourism in forming Gambang Semarang as an art identity in the City of Semarang. Various efforts have been made by referring to the five strategies for advancing culture stated in the law, and 4 of the five strategies have started to run starting from efforts: 1) Preservation, 2) Development, 3) Utilization, and 4) Coaching. This study examines and describes the Semarang City government's strategy in implementing a cultural preservation strategy to preserve Gambang Semarang. This study uses a qualitative descriptive method. Data collection in this study was obtained through observation, interview, and documentation techniques. Data was analyzed using interactive analysis techniques. The validity of the data was tested using source triangulation techniques, technical triangulation, and time triangulation. The results of the study indicate that Gambang Semarang needs to be endeavored so that it can be preserved sustainably from various aspects until the identity of Semarang is formed from the art of Gambang Semarang itself.